Senegalese students’ attitudes toward English and Arabic: A comparative analysis - Abdelatif ABILKASSEM (Moroccan Journal of Quantitative and Qualitative Research)
This study investigated the attitudes toward Arabic and English among Senegalese students in Cheikh Anta Diop University (UCAD) in Dakar. Data were collected through a questionnaire completed by 100 respondents. The findings suggest that overall, Senegalese students held highly positive attitudes toward English. Students are both instrumentally and integrally motivated to learn this language. They manifested a great interest to learn it. They also agree that it is the language of economy and scientific research. On the other hand, Students held a mixture of positive and negative attitudes toward Arabic. While the majority of respondents show positive attitudes toward learning this language and its religious role, they manifested negative attitudes toward the ability of Arabic to insure job opportunities or academic achievements.